In the ice caves of Krog - Abbott, Tony.; Adams, Gil (New York, NY : Scholastic, 2003)
Way up north in the ice caves of Droon lives a nasty, snowy beast. Krog has just woken up from a long nap, and boy, is he grouchy! Eric and his friends have to stop the monster from causing too much trouble. But when they reach the magical ice caves, they discover that Krog is not exactly the beast they were expecting...
"A Little Apple paperback."
6 8 9 13
Keywords: Magic -- Fiction; Fantasy